Systemic therapy with or without transcatheter intra-arterial therapies for unresectable hepatocellular carcinoma: a real-world, multi-center study - Pan, Yangxun; Zhu, Xiaodong; Liu, Jianwei; Zhong, Jianhong; Zhang, Wei; Shen, Shunli; Jin, Renan; Liu, Hongzhi; Ye, Feng; Hu, Kuan; Xu, Da; Zhang, Yu; et al. (Frontiers in Immunology, 2023)
Background Systemic therapy is the standard care of unresectable hepatocellular carcinoma (uHCC), while transcatheter intra-arterial therapies (TRITs) were also widely applied to uHCC patients in Chinese practice. However, the benefit of additional TRIT in these patients is unclear. This study investigated the survival benefit of concurrent TRIT and systemic therapy used as first-line treatment for patients with uHCC. Methods This real-world, multi-center retrospective study included consecutive patients treated at 11 centers accross China between September 2018 and April 2022. Eligible patients had uHCC of China liver cancer stages IIb to IIIb (Barcelona clinic liver cancer B or C stage), and received first-line systemic therapy with or without concurrent TRIT. Of 289 patients included, 146 received combination therapy and 143 received systemic therapy alone. The overall survival (OS), as primary outcomes, was compared between patients who received systemic therapy plus TRIT (combination group) or systemic therapy alone (systemic-only group) using survival analysis and Cox regression. Imbalances in baseline clinical features between the two groups were adjusted through propensity score matching (PSM) and inverse probability of treatment weighting (IPTW). Moreover, subgroup analysis was conducted based on the different tumor characteristics of enrolled uHCC patients. Results The median OS was significantly longer in the combination group than the systemic-only group before adjustment [not reached vs. 23.9 months; hazard ratio (HR), 0.561; 95% confidence interval (CI), 0.366 to 0.861; P = 0.008], after PSM (HR, 0.612; 95% CI, 0.390 to 0.958; P = 0.031) and after IPTW (HR, 0.539; 95% CI, 0.116 to 0.961; P = 0.008). Subgroup analyses suggested the benefit of combining TRIT with systemic therapy was greatest in patients with liver tumors exceeding the up-to-seven criteria, with an absence of extrahepatic metastasis, or with alfa-fetoprotein ≥ 400 ng/ml. Conclusion Concurrent TRIT with systemic therapy was associated with improved survival compared with systemic therapy alone as first-line treatment for uHCC, especially for patients with high-intrahepatic tumor load and no extrahepatic metastasis.